Redistribution, Demand, and Sustainable Production - Sonja Dobkowitz (ZBW - Leibniz Information Centre for Economics, 2022)
Recent evidence points to an increase in consumers' willingness to pay for sustainable goods, i.e., social responsibility. What is the optimal policy response to such a shift in preferences? Advancing social responsibility suggests a demand-driven transition to sustainable production. This paper argues, however, that basic needs and income inequality pose an obstacle. Therefore, (i) lump-sum transfers alter the share of sustainable production, and (ii) social responsibility exacerbates consumption inequality. In the model, inequality renders labour taxes part of the optimal environmental policy for all levels of social responsibility. Greater social responsibility entails a policy shift away from corrective taxation towards redistribution. The aggravation of consumption inequality turns the policy focus on equity. As a consequence, redistribution arises as the central pillar of the optimal environmental policy.
Keywords: E71; H21; H23; Q58; 330